设a,b,c为非零实数,且|a|+a=0,|ab|=ab,|c|-c=0 化简|b|-|a+b|-|c-b|+|a-c|

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 06:32:20
设a,b,c为非零实数,且|a|+a=0,|ab|=ab,|c|-c=0化简|b|-|a+b|-|c-b|+|a-c|设a,b,c为非零实数,且|a|+a=0,|ab|=ab,|c|-c=0化简|b|

设a,b,c为非零实数,且|a|+a=0,|ab|=ab,|c|-c=0 化简|b|-|a+b|-|c-b|+|a-c|
设a,b,c为非零实数,且|a|+a=0,|ab|=ab,|c|-c=0 化简|b|-|a+b|-|c-b|+|a-c|

设a,b,c为非零实数,且|a|+a=0,|ab|=ab,|c|-c=0 化简|b|-|a+b|-|c-b|+|a-c|
|a|+a=0 -----> a ab>0,b c>0
|b|-|a+b|-|c-b|+|a-c|
=-b+a+b-c+b-a+c
=b

a,b,c为非零实数,且|a|+a=0,|ab|=ab,|c|-c=0 ;
那么a<0,b<0,c>0;
∴|b|-|a+b|-|c-b|+|a-c| =-b+a+b-c+b-a+c=b